Pendidikan Agama Islam Sebagai Sarana Membentuk Generasi Qur’an di Ma’had Al-Jamiah - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Agus Agus; Habibatul Inayah; Sepralin Tesva (Pusat Riset dan Inovasi Nasional, 2023)
This research is entitled Islamic Religious Education as a means of forming the Qur'anic generation in Ma'had Al-Jami'ah. The aim of this research is to find out the function of Islamic religious education in creating a Qur'anic generation. The results obtained are that there are many activities carried out at Ma'had Al-Jami'ah to form the Qur'ani generation. These activities are to provide a deep understanding of Islamic teachings and be able to apply them in everyday life. Especially in the context of Muslims, Islamic religious education plays a very important role in shaping the morals and values ​​of the younger generation. In an effort to produce quality generations of Al-Qur'an, it will also study Al-Qur'an memorization, Al-Qur'an understanding, application of Al-Qur'an ideals, and integration of Islamic religious education with general education.